Compensating the Losers of Globalisation - Zareh Asatryan; Sebastian Braun; Holger Görg; Friedrich Heinemann; Hassan Molana; Catia Montagna (WWWforEurope, 2014)
Fears of job losses and of increasing inequality loom large in current debates on how globalization is affecting our economies. By fundamentally changing the organization of production and work, globalization creates complex and changing patterns of winners and losers. Globalization thus creates powerful challenges to welfare states and may increase the demand for redistributive policies. At the same time, conventional wisdom suggests that increasing globalisation requires a reduction in the provision of the welfare state among industrialised countries as the distortions resulting from this type of expenditure undermine international competitiveness and the ability of countries to attract and/or retain industries. Against this background, the aim of the policy brief is two-fold. First, it will describe the likely winners and losers of the globalization process in terms of labor market outcomes. The policy brief will focus on one particularly important aspect of globalization, namely on increasing international trade flows, and will review the evidence on the effect of trade on inequality. Second, the policy brief will propose and discuss policy measures to compensate the losers of globalization. Ideally, these policy measures will spread the benefits of globalization more equally in society without undermining a country's international competitiveness.
Keywords: F10; F20; J30; J60; 330; Challenges for welfare system; Globalisation; Labour markets; Welfare state